KONTRIBUSI PEREMPUAN TERHADAP PERTUMBUHAN EKONOMI MELALUI KELOMPOK WANITA TANI: Studi Kasus di Desa Mekarwangi Kecamatan Saketi Kabupaten Pandeglang - Fahmi Andaluzi; Ika Atikah; Dhea Salsabila Syifa; Yunita Sa'dataen; Safiq Al Kalam (LP2M Universitas Ibrahimy, 2024)
This research aims to explore the role of women towards economic empowerment through Women Farmers Group (KWT). This research uses a qualitative approach with PAR (Participatory Action Research) analysis, the research was conducted in Mekarwangi village, Saketi District, Pandeglang Regency. Data was collected through interviews and participatory observation. The results showed that KWT is not only a forum for women in empowering and increasing family income, but also provides space for them to develop skills, build social networks, and increase roles in the public sector, especially agriculture. Through KWT, women in Mekarwangi Village have managed to develop their individual and cooperative skills in managing businesses, such as managing agricultural fields, farming to marketing and managing the money from sales. So that they can increase their role from just being a housewife to an active economic actor in a more complex sector. This research concludes that Women Farmers Groups have great potential in empowering women and promoting gender equality, especially at the village level.